Inovasi Media Pembelajaran Biologi: Validasi Poster Virus pada Materi Mikroorganisme Kelas X - Matovani Ilham As'ad; Mucharommah Sartika Ami; Anggun Wulandari (Program Studi Pendidikan Biologi Universitas Katolik Widya Mandira, 2025)
This study aims to describe the feasibility of virus posters as learning media for grade X students based on the validation results of material experts and learning media experts. This study is a development research using the ADDIE model. Data collection was carried out using a questionnaire technique. The instruments used were material expert validation sheets and learning media expert validation sheets. The validators of material experts and learning media experts involved in this study were one lecturer each with expertise in the field of viruses and the field of biology learning media development. The data collected were in the form of scores and suggestions from both validators, which were analyzed descriptively. The results showed that the developed virus poster met the criteria for feasibility with moderate revisions based on the results of material expert validation (average score of 76.00); and met the criteria for feasibility with minor revisions based on the results of learning media expert validation (average score of 89.09). This indicates that the developed virus poster is suitable for use as a learning media for grade X students.